The Influence of Financial Literacy, Financial Inclusion, and Financial Attitude on the Financial Performance of Depok UMKM Through Financial Management as an Intervening Variable - Annisa Diana Putri; Elwisam Elwisam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study was to analyze and obtain empirical evidence of the influence of financial literacy, financial inclusion, and financial attitudes on the financial performance of Depok UMKM through financial management as an intervening variable. The research used a purposive sampling method to select samples for the UMKM (Micro and Medium Enterprises) Depok Region registered with DKUM (Department of Micro Enterprise Cooperatives). The data analysis method used is Structural Equation Modelling-Partial Least Squares (SEM-PLS) on WarpPLS 7.0 application software. The results of this study state that financial literacy has a significant positive direct influence on the financial performance of Depok UMKM, Financial Inclusion has an insignificant positive influence on the financial performance of Depok UMKM, Financial attitudes have an insignificant positive influence on the financial performance of Depok UMKM, Financial literacy has a significant positive direct influence on financial management, financial inclusion has a significant positive direct influence in financial management, the financial attitude has a significant positive direct influence on financial management, financial management has a positive and significant direct influence of financial performance, financial management is able to mediate financial literacy on financial performance, financial management is not able to mediate financial inclusion on financial performance and financial management are able to mediate financial attitudes toward financial performance.